Trajetória de vida educacional e os desafios da atuação profissional da EJA (Educação de Jovens e Adultos) - LIMA, Selma Oliveira (2023)
Make a memorial is to build your own existence. This is not an easy task. Therefore, in preparing this memorial I took into account the criticism and self-criticism of academic performance throughout my career. In this opportunity, I seek to highlight the elements marked by paradigm breaks, by coherence and inconsistencies, and through established relationships with the world, enabled me to construct my trajectory that involves both personal and professional. The challenge is to rescue fragments of the past conscious and "unconscious" experiences that come to give life to the memorial of trajectory and the transformations perceived in the course of past and present experiences. In addition to considering this high-evaluative memorial, I believe it eventually becomes a confessional instrument of my dreams.